A new Miocene carnivorous marsupial, Barinya kutjamarpensis (Dasyuromorphia), from central Australia. Issue 1 (2nd January 2017) - Binfield, Pippa; Archer, Michael; Hand, Suzanne J.; Black, Karen H.; Myers, Troy J.; Gillespie, Anna K.; Arena, Derrick A.
Abstract : Binfield, P., Archer, M., Hand, S.J., Black, K.H., Myers, T.J., Gillespie, A.K. & Arena, D.A., June 2016. A new Miocene carnivorous marsupial, Barinya kutjamarpensis (Dasyuromorphia), from central Australia. Alcheringa 41, xx–xx. ISSN 0311-5518. A new dasyuromorphian, Barinya kutjamarpensis sp. nov., is described on the basis of a partial dentary recovered from the Miocene Wipajiri Formation of northern South Australia. Although about the same size as the only other species of this genus, B. wangala from the Miocene faunal assemblages of the Riversleigh World Heritage Area, northwestern Queensland, it has significant differences in morphology including a very reduced talonid on M4 and proportionately wider molars. Based on the structural differences and the more extensive wear on its teeth, the central Australian species might have consumed harder or more abrasive prey in a more silt-rich environment than its congener, which hunted in the wet early to middle Miocene forests of Riversleigh. Pippa Binfield [ pippa.binfield@outlook.com ], Michael Archer [ m.archer@unsw.edu.au ], Suzanne J. Hand [ s.hand@unsw.edu.au ], Karen H. Black [ k.black@unsw.edu.au ], Troy J. Myers [ t.myers@unsw.edu.au ] Anna K. Gillespie [ a.gillespie@unsw.edu.au ] and Derrick A. Arena [ rick@sitc.net.au ], PANGEA Research Centre, School of Biological, Earth and Environmental Sciences, University of New South Wales 2052, Sydney, Australia.